LEGAL REGULATION OF CONSTRUCTION ACTIVITY - R. Ganeyev (Russian Journal of Economics and Law)
The article reveals topical issues of legal regulation of construction activity. The author proposes his definition of construction activity notion and characterizes the main stages of construction activity and features of their legal regulation.